2017
DOI: 10.1021/acs.energyfuels.7b02866
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Chloride Hexahydrate/Diatomite/Paraffin as Composite Shape-Stabilized Phase-Change Material for Thermal Energy Storage

Abstract: In this work, the calcium chloride hexahydrate/diatomite/paraffin composite phase-change material (PCM) was fabricated by impregnating calcium chloride hexahydrate into diatomite and further coating with paraffin. Scanning electron microscope (SEM) results showed that the hydrated salt could be impregnated into a diatomite well and the paraffin could be coated on a diatomite surface. The Fourier transform infrared spectroscopy (FT−IR) demonstrated that no chemical interactions were found between calcium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Chemical degradation of PCMs is reported in several papers under the name of thermal stability studies . In all of them, TGAs are performed under inert atmosphere (N 2 or Ar) at a single heating rate (normally 10°C/min) in order to obtain the temperature limit for the beginning of PCM degradation.…”
Section: Service Conditions and Degradation Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical degradation of PCMs is reported in several papers under the name of thermal stability studies . In all of them, TGAs are performed under inert atmosphere (N 2 or Ar) at a single heating rate (normally 10°C/min) in order to obtain the temperature limit for the beginning of PCM degradation.…”
Section: Service Conditions and Degradation Factorsmentioning
confidence: 99%
“…According to this review, most tested PCMs are intended for storage applications at temperatures below 100°C. Those PCMs include pure substances, eutectic mixtures, and composites that undergo either solid‐liquid or solid‐solid phase transitions. In contrast, only few stability studies have been found for PCMs intended to temperature applications above 100°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the aim to avoid leakage, researchers have developed various methods to encapsulate PCMs, such as direct adsorption, capsulation, and sol‐gel method . The direct adsorption method is commonly to use porous materials as carriers, such as expanded graphite, perlite, montmorillonite, bentonite, and diatomite .…”
Section: Introductionmentioning
confidence: 99%
“…There into, inorganic PCM have some attractive properties such as larger latent heat density, higher heat conductivity, and lower material cost compared with organics. However, phase separation and supercooling are two severe problems of hydrated salts for technical application . The conventional methods to solve above problems are utilization of thickening and nucleating agents .…”
Section: Introductionmentioning
confidence: 99%